Stevens-Johnson Syndrome Associated With Chlordiazepoxide. (April 2018) - Jawaro, Tara; Kumar, Ayan; Pistun, Oleksandr; Dixit, Deepali
Objective: To report a case of chlordiazepoxide-associated Stevens-Johnson syndrome (SJS).Case Summary: This case provides insight into a serious adverse drug reaction secondary to a drug not commonly associated with SJS. A 29-year-old female presented with a 4-day history of rash and pruritus. The rash started on her arms and spread all over her body. The patient was started on chlordiazepoxide 3½ weeks ago. On examination, there were multiple, raised, round erythematous lesions in various stages of healing. Skin erosions were noted on her lips and buccal mucosa. However, the rash did not involve the conjunctiva, inner ears, or genitalia. The patient was discharged home with a follow-up appointment with dermatology and instructions to discontinue chlordiazepoxide. Two days after her initial presentation, the patient's rash spread to her eyes and genitalia. A painful, white film developed on her tongue, and she was unable to tolerate oral intake. She was emergently sent back to hospital and transferred to a Burn Unit. The biopsy report revealed full-thickness necrotizing keratinocytes in the epidermis consistent with SJS.Discussion: To our knowledge, there is only one other case report of chlordiazepoxide-associated SJS. Chlordiazepoxide is thought to be the cause of this patient's biopsy-confirmed SJS and overall presentation. SJS is a rare but serious condition that is usually a result of drug exposure.Conclusions: The close temporal relationship between chlordiazepoxide initiation and onset of SJS provides a convincing theory as to the etiology of SJS in our patient.